Озерные страсти: роман / Татьяна Алюшина - Алюшина Татьяна Александровна (Экcмо, 2021)
Экземпляры: ЦБ; ф15 (20210615) / Инвентарный номер: 61078 / Цена: 252.00 / Сис.шифр: Р2 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6